STRUKTUR KOMUNITAS COLLEMBOLA TANAH DI KAWASAN HUTAN CAGAR ALAM TANGALE KABUPATEN GORONTALO - Muhamad Iksan; Ramli Utina; Abubakar Sidik Katili (Jambura Edu Biosfer Journal, 2019)
This study aimed to determine the community structure of soil Collembola found in Tangale Nature Preserve. The method used in this study is descriptive and quantitative data collection using the line transect is divided into two stations and each station there were 10 sampling plots, using a trap. Data were processed using the formula struktrur community dominance index (ID), Diversity Index (H?), abundance index (J?) and the Density Index (Di) . The results showed that the structure of soil Collembola communities in the Nature Preserve in the midle categories being Tangale. If viewed from the diversity index shows the number 1.377 and 1.374. To the dominance of family Entomobryidae sp. 1 with 0.015 Indv/m2 dominance index, family Entomobryidae sp. 2 with 0.013 Indv/m2 dominance index, family Entomobryidae sp. 3 with 0.07 Indv/m2 dominance index, and family Paronellidae 0.014 sp Indv/m2 dominance index. With an average of 0.253 Indv/m2. for the abundance, family Entomobryidae sp. 1 at 0.512 Indv/m2, and which has the lowest abundance value of the index family believe Entomobryidae sp. 3 of 0.458 Indv/m2. As for the value of the density of family Entomobryidae sp. 1 with a density of 0.0098 Indv/m2 index, family Entomobryidae sp. 2 with a density of 0.0098 Indv/m2 index, family Entomobryaidae sp. 3 with a density of 0.0012 Indv/m2 index, and family Paronellidae sp index Indv/m2 density of 0.0098. The results showed that the structure of soil Collembola communities in the Nature Preserve in the midle categories being Tangale.